Analisis teori norms life-cycle dalam proses difusi norma bisnis bertanggung jawab di ASEAN - Azzahra, Salwa (Journal of Economic, Business & Accounting Research, 2024)
Corporate Social Responsibility (CSR) has emerged as a significant concept in understanding responsible business practices carried out by Multinational Corporations (MNCs). According to the World Business Council on Sustainable Development (WBCSD), CSR is defined as a continuous commitment by businesses to behave ethically, contribute to economic development, improve the quality of life for their employees, and enhance the well-being of the surrounding communities. In the current landscape, many MNCs wield more influence and power than entire nations, even global institutions like the United Nations (UN). Consequently, CSR has become a crucial issue, reflecting the accountability of various MNCs in the eyes of the public. Over time, CSR has been increasingly adopted by business leaders as an integral part of their operations, driven by the realization that businesses must make a positive contribution to solving societal issues. The extensive discussion surrounding CSR has given rise to multiple perspectives, ranging from a managerial perspective within companies to a global norm acknowledged by various international actors. These perspectives began to take shape in the 1970s, fueled by rapid industrialization and the emergence of social and environmental movements, particularly those advocating for workers' rights.